Learning Readiness Assessment Framework In Promoting E-Health Engagement Among Libyan Nurses - Mohamed Elhadi, M. Sharif (2014)

(untitled)
The use of e-health services by the Libyan government has become of high concern recently. This study focused on how the main factors or elements of working capacity in terms of structural environment, technological availability, and other competence-related issues may influence nurses’ engagement in e-health. Therefore, this research was established to build a learning readiness assessment framework (LRAF) for Libyan regional hospitals based on the adaptation of e-health services in nursing education. Penggunaan perkhidmatan e-Kesihatan oleh kerajaan Libya telah menerima perhatian yang tinggi kebelakangan ini. Kajian ini memfokuskan kepada cara faktorfaktor utama atau unsur-unsur keupayaan bekerja dari segi persekitaran struktural, ketersediaan teknologi, dan isu-isu lain yang berkaitan dengan kecekapan mempengaruhi penglibatan jururawat dalam penggunaan e-Kesihatan.